Individual-level and group-level mediators of contact effects in Northern Ireland: the moderating role of social identification. - Tausch, N; Tam, T; Hewstone, M; Kenworthy, J; Cairns, E (2007)
We tested a model which considered individual-level (intergroup anxiety) and group-level (perceived realistic and symbolic threats to the in-group) threats as simultaneous mediators in the relationship between the quantity and quality of cross-community contact and intergroup attitudes (Study 1, N=166) and trust (Study 2, N=163) in Northern Ireland. The studies tested the hypothesis that the strength of group-identification moderates the importance of individual- vs. group-level threats as predictors of attitudes and trust and as mediators of contact effects. Both anxiety and symbolic threat, but not realistic threat, emerged as predictors of the criterion variables and mediated contact effects. Our results provide support for the moderating role of identification and suggest that while symbolic threat predicts attitudes and trust for high, but not low identifiers, anxiety is a somewhat more important predictor for low than for high identifiers. We discuss these results against the background of current intergroup relations in Northern Ireland.